Informality as Fix: Repurposing Jugaad in the Post-Crisis Economy. Issue 1 (2nd January 2018) - Badami, Nandita
Abstract: Street cultures of make-do and reuse in contemporary India, colloquially known as jugaad, is a set of material practices that have had a long and established history in the country. This article juxtaposes such practices with 'repair' in order to consider the politics of jugaad as it played out in the years following the financial crisis of 2008. As growth rates suffered massive contractions and workers were laid off in large numbers, jugaad came to take on cultural valences in unexpected contexts, especially within business management literature, where it signalled the vibrancy of the 'informal' economy. Following the migration of the term into widespread English usage, alongside the parallel, growing demand for the 'right to repair' in the United States and Europe, this article traces how an undisciplined, subaltern practice of repurposing came to be repurposed, in turn, in the service of the failing 'formal' economy.